2019
DOI: 10.4049/jimmunol.1800750
|View full text |Cite
|
Sign up to set email alerts
|

UBL4A Augments Innate Immunity by Promoting the K63-Linked Ubiquitination of TRAF6

Abstract: Human UBL4A/GdX, encoding an ubiquitin-like protein, was shown in this study to be upregulated by viral infection and IFN stimulation. Then the functions of UBL4A in antiviral immune response were characterized. Overexpression of UBL4A promoted RNA virus-induced ISRE or IFN-b or NF-kB activation, leading to enhanced type I IFN transcription and reduced virus replication. Consistently, knockdown of UBL4A resulted in reduced type I IFN transcription and enhanced virus replication. Additionally, overexpression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Ubl4A is a multifunctional protein that is involved in diverse cellular events, from translocation of newly synthesized proteins to the ER, DNA damage repair, bone modeling, inflammatory and innate immune response, to anti-tumorigenesis [40][41][42][43][44][45][46][47][48]. Here, we showed that under nutrient starvation conditions, Ubl4A functions as a survival factor mainly by regulating the mitochondrial fusion process.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ubl4A is a multifunctional protein that is involved in diverse cellular events, from translocation of newly synthesized proteins to the ER, DNA damage repair, bone modeling, inflammatory and innate immune response, to anti-tumorigenesis [40][41][42][43][44][45][46][47][48]. Here, we showed that under nutrient starvation conditions, Ubl4A functions as a survival factor mainly by regulating the mitochondrial fusion process.…”
Section: Discussionmentioning
confidence: 97%
“…Although it belongs to the ubiquitin-like family, Ubl4A has no ubiquitination activity [39]. Instead, this protein has diverse functions, from chaperoning nascent synthesized proteins to the ER, promoting anti-tumorigenesis, potentiating autoimmune diseases, to augmenting innate immune response through NFκB signaling pathway [40][41][42][43][44][45][46][47][48]. We have shown that Ubl4A can directly interact with the Arp2/3 complex to promote actin branching [49].…”
Section: Introductionmentioning
confidence: 99%
“…regulating a series of physiological process (35)(36)(37)(38)(39)(40). In addition, the oncogenic role of TRAF6 in tumors has been widely reported.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the viral nucleic acid sensor RIG-I is activated by K63-polyubiquitination mediated by the ligases TRIM4 [ 45 ], Riplet [ 46 ], and TRIM25 [ 47 ], while signaling is terminated by K48-polyubiquitination mediated by the Ring Finger protein 125 (RNF125) ligase [ 48 ], which promotes proteasomal degradation. The attachment of M1- or K63-polyubiquitin chains to signaling mediators such as IRAK1 (Interleukin 1 associated kinase-1) [ 49 , 50 ], TRAF6 [ 51 ], RIP1 (Receptor interacting protein-1) [ 52 ], TRAF3 (TNF receptor associated factor-3) [ 53 ], MAVS (Mitochondrial antiviral signaling protein) [ 54 ], NEMO (NF-κB essential modulator) [ 55 ], and STING (Stimulator of IFN genes) [ 56 ] promotes activation of the kinases IKK (IκB kinase), TAK1 (Transforming growth factor beta activated kinase-1), and TBK1 (TANK binding kinase-1) [ 57 , 58 ] that phosphorylate the executor transcription factors NF-κB (Nuclear factor-κB, IRF3 (Interferon regulatory factor-3), and IRF7, leading to their activation and nuclear translocation. Phosphorylation may also serve as a signal for ubiquitination as illustrated by the phosphorylation-dependent K48-polyubiquitination of IκBα by the βTRCP E3 ligase, which leads to degradation of the inhibitor and activation of NF-κB [ 59 ].…”
Section: Ubls In Viral Infectionmentioning
confidence: 99%